Własności Mechaniczne Kilku Modeli Gruntów - Biarez, J. (Engineering Transactions, 1964)
This paper is devoted to the description and analysis of some results concerning problems of granular bodies representing continuous bodies. The test have been performed by means of samples composed of parallel glass rods of circular or polygonal cross-section, glass balls or sand. The dimension of these elements were so small, that the properties of the model were practically those of a continuum, qualitatively at least. Mechanical properties of the bodies tested depend on the arrangement of elements, elastic properties of grains (or elements) angle of internal friction material used etc.